Targeting tumor-associated myeloid cells for cancer immunotherapy - Qin, Hong (Oncoimmunology, 2015)
Tumor-associated myeloid cells undermine the therapeutic efficacy of cancer immunotherapy by their inhibitory properties on immune effector cells. Development of therapeutic agents to deplete suppressive myeloid cells in tumor microenvironment requires identification of cell-specific targets. A competitive phage display technique on live cells paves the way to discovery of such a target.